Screening of indigenous methicillin-resistant Staphylococcus aureus (MRSA)-inhibiting actinomycetes from Sicanang Mangrove and Cermin Beach in North Sumatra Province, Indonesia - YURNALIZA YURNALIZA; ERMAN MUNIR; RIRIS ITA OLIVIA GULTOM; ANDINI JUNIASTI NASUTION (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Yurnaliza Y, Munir E, Gultom RO, Nasution AJ. 2024. Screening of indigenous methicillin-resistant Staphylococcus aureus (MRSA)-inhibiting actinomycetes from Sicanang Mangrove and Cermin Beach in North Sumatra Province, Indonesia. Biodiveritas 25: 3401-3410. Methicillin-resistant Staphylococcus aureus (MRSA) is the major issue of antimicrobial resistance in medical practice. Unexplored locations like the Sicanang mangrove and Cermin beach in North Sumatra, Indonesia are expected to find indigenous actinomycetes as MRSA-inhibiting antibiotics producers. This study aims to explore the potential of actinomycetes in North Sumatra, especially in the Sicanang Mangrove forest and Cermin Beach, in inhibiting the growth of MRSA. Actinomycetes were isolated and characterized using starch casein agar and humic acid vitamin agar. Actinomycetes that inhibit MRSA and S. aureus (ATCC 25923) bacteria were qualitatively screened using an antagonist test. Subsequently, the inhibitory activities of methanol (MeOH) and ethyl acetate (EtOAc) actinomycetes extracts against MRSA and S. aureus were quantitatively monitored. The potential actinomycetes with the highest inhibitory ability were identified based on their 16S rRNA gene sequence. The research revealed 30 isolates capable of inhibiting MRSA and S. aureus. Among them, 10 actinomycetes isolates inhibited MRSA and S. aureus, with inhibition zone diameters ranging from 15 to 28 mm. Moreover, MeOH and EtOAc actinomycetes extracts produced a similar inhibition zone (7-20.8 mm against MRSA and S. aureus). Although a concentrated extract produced a large inhibition zone, the zone was smaller than that produced by chloramphenicol. Molecular identification showed that the potential actinomycetes, particularly SMC 9, were closely related to Streptomyces rochei, with a similarity of 96.02%, while SPC 9 had a high similarity (99%) with Streptomyces antibioticus. Based on research findings, two species of Streptomyces obtained from the Sicanang mangrove and Cermin Beach could be developed as producers of MRSA-inhibiting antibiotics.